Animal Satire in Nabatah and Hollow Kingdom: A Comparative Analysis (Malay Literature, 2023)
Each nation has its own animal tales that have been passed down since oral literature period. Animal tales are classified into several forms such as animal origin stories, educational fables, animal myths, and animal satires or allegories. For instance, animal tales, whether satirical or figurative, are created to criticise the weaknesses of an individual or an authority so they may improve. Nonetheless, previous studies that have compared Malaysian and American animal tales as satire are lacking. This gap needs to be filled since such a study can promote animal characters from both countries besides highlighting the uniqueness of both stories in their different languages, cultural backgrounds, and places. This article discusses the novels Nabatah from Malaysia and Hollow Kingdom from the United States of America. The objective of this study is to identify and analyse the issues of social deprivation presented in the texts through the animal characters. The concept of satire was utilised to conduct the evaluation. The results demonstrated that the issues of social deprivation presented by each author reflect the reality of societal deterioration in both nations that must be addressed. This discovery proves that animal satire has the potential to be an effective and indirect means of public criticism.